Artificial Intelligence (AI) on Accountant Behavior and Ethical Decision Making: Systematic Review on Behavioral Accounting Research - Nordiansyah, Muhammad; Arifuddin, Arifuddin; Mediaty, Mediaty (Economics, Business, Accounting & Society Review, 2025)
The advancement of Artificial Intelligence (AI) has significantly transformed accounting practices by automating routine tasks, enhancing anomaly detection, and influencing professional decision-making processes. This transformation is not purely technical; it introduces critical ethical challenges, including algorithmic bias and shifts in professional identity among accountants. This study aims to evaluate the impact of AI on accountants’ behavior, ethical reasoning, and decision-making within the framework of Behavioral Accounting Research (BAR). A combined method of Systematic Literature Review (SLR) and bibliometric analysis was employed, reviewing 47 selected articles from the Scopus database between 2015 and 2025. The findings reveal that AI affects three major dimensions of accountant behavior: cognitive bias due to overreliance on AI recommendations, a decline in professional skepticism, and an identity shift from traditional accounting roles to AI interpreters. Bibliometric analysis identified six key thematic clusters, including AI literacy, accounting education, technology adoption, AI-driven auditing, and ethical implications in digital accounting practice. Keyword co-occurrence visualization further highlights ethics, trust in AI, and algorithmic bias as central topics in current accounting discourse. The main findings indicate that the adoption of AI is shaped by users’ technological readiness, trust in AI systems, and awareness of ethical risks. Furthermore, the study emphasizes the importance of integrating both technological and ethical literacy into accounting education curricula. The implication of this research is the need to develop new theoretical models that combine behavioral ethics with human–AI interaction to ensure responsible and ethically grounded AI adoption in the accounting profession.